2014
DOI: 10.1016/j.surg.2014.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality in patients with esophageal atresia

Abstract: Background This study reports national estimates of population characteristics and outcomes for patients with EA/TEF and evaluates relationships between hospital volume and outcomes. Methods Patients admitted within 30 days of life who had ICD-9-CM diagnosis and procedure codes relevant to EA/TEF during 1999–2012 were identified using the Pediatric Health Information System database. Baseline demographics, comorbidities, and post-operative outcomes, including predictors of in-hospital mortality, were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 25 publications
9
87
0
5
Order By: Relevance
“…3,[9][10][11]28 In general, the postoperative mortality seems to be more reflective of a center's overall neonatal expertise rather than the operative management itself as recently demonstrated by a nationwide study of 3479 children with EA/TEF across the United States. 8 Because of its rarity and complex nature, EA/TEF represents one of the major therapeutic challenges not only in modern pediatric surgery but also for other specialties involved due to serious short-and long-term morbidities. [13][14][15][16][17][18] Our results were consistent with previous studies indicating that despite precise esophageal reconstruction and excellent postoperative care, early and late complications frequently occur and must be dealt with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[9][10][11]28 In general, the postoperative mortality seems to be more reflective of a center's overall neonatal expertise rather than the operative management itself as recently demonstrated by a nationwide study of 3479 children with EA/TEF across the United States. 8 Because of its rarity and complex nature, EA/TEF represents one of the major therapeutic challenges not only in modern pediatric surgery but also for other specialties involved due to serious short-and long-term morbidities. [13][14][15][16][17][18] Our results were consistent with previous studies indicating that despite precise esophageal reconstruction and excellent postoperative care, early and late complications frequently occur and must be dealt with.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Due to the complex nature and infrequency of cases, EA/TEF management remains a major therapeutic challenge for most pediatric surgeons and other involved specialists. 5,6 In most of the current reports, prematurity, low birth weight, and additional congenital anomalies are associated with higher mortality and further complicate the care of these patients, 7,8 whereas survival rates in full-term infants with no other abnormalities can approach 100% after EA/TEF surgery. 9,10 Today, improved survival of newborns with EA/TEF is likely related to multiple factors including advances in neonatal intensive care and anesthesia, refined surgical techniques, parenteral nutrition, and antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many are prematurely born or are small for gestational age (SGA) (4,17). The current literature is not conclusive regarding the specific contributions of these factors to growth.…”
Section: Factors That Influence Long-term Growth In Oamentioning
confidence: 99%
“…In the 1950s and 1960s the neonatal mortality rates were approximately 35%; severe bronchopneumonia was the main cause of death (3). Due to better surgical techniques and intensive care treatment, mortality has dropped to less than 10% today (4,5), with severe associated chromosomal defects and complex cardiac defects as main causes of death. With decreasing mortality rates attention has shifted towards long-term morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous pioneering study, endoscopic findings influenced the operative procedure in more than 57 patients [6]. In a recent large multicenter study, the reported rate of repeated TEF repairs was 5.4% within 2 years; however later recurrences may still occur [7] [8]. This statistic includes relapses due to recanalization of the original fistula as well as missed proximal TEFs after the repair of Gross type C atresia.…”
Section: Tracheobronchoscopymentioning
confidence: 99%